2016
DOI: 10.1103/physrevlett.117.215501
|View full text |Cite
|
Sign up to set email alerts
|

Nanobubble Fragmentation and Bubble-Free-Channel Shear Localization in Helium-Irradiated Submicron-Sized Copper

Abstract: Helium bubbles are one of the typical radiation microstructures in metals and alloys, significantly influencing their deformation behavior. However, the dynamic evolution of helium bubbles under straining is less explored so far. Here, by using in situ micromechanical testing inside a transmission electron microscope, we discover that the helium bubble not only can coalesce with adjacent bubbles, but also can split into several nanoscale bubbles under tension. Alignment of the splittings along a slip line can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 29 publications
0
39
0
Order By: Relevance
“…A NB-Cu sample with width of %150 nm was cyclically loaded along its 1 82 ½ direction using a specially designed push to pull sample geometry in order to achieve stable in situ loading on a thin TEM foil, [55] as shown in Figure 4. In the first tensile loading segment, the sample shear localizes along two major slip planes, marked in Figure 4b as "twin" and "slip" (more obvious in movie S4).…”
Section: Twinning and Detwinning In Helium Irradiated Cu Under Cyclicmentioning
confidence: 99%
See 1 more Smart Citation
“…A NB-Cu sample with width of %150 nm was cyclically loaded along its 1 82 ½ direction using a specially designed push to pull sample geometry in order to achieve stable in situ loading on a thin TEM foil, [55] as shown in Figure 4. In the first tensile loading segment, the sample shear localizes along two major slip planes, marked in Figure 4b as "twin" and "slip" (more obvious in movie S4).…”
Section: Twinning and Detwinning In Helium Irradiated Cu Under Cyclicmentioning
confidence: 99%
“…Conversely, the samples with polyslip orientation, marked on lines (011)-(111) and (001)-(111), can deform either by twinning or full dislocation slip. [55] It should be mentioned that the size effect observed in NB-Cu pillars is different from the very weak size effect observed in pillars containing shear-resistant particles [56][57][58][59][60] as the current NB-Cu pillar contains helium bubbles can be cut through by dislocations at elevated stresses, which could induce some extent of size-dependence as the Cu pillars containing high density of irradiation induced stacking fault tetrahedrals. In that context, the CRSS for twinning, detwinning and slipping in NB-Cu and FD-Cu single crystals under compressive or tensile loading is plotted as a function of sample size in Figure 5b.…”
Section: Orientation and Sample Size Effect On Plasticity Of Helium Imentioning
confidence: 99%
“…A variety of in situ TEM specimen geometries have been demonstrated on irradiated materials, including indentation [12], tensile [13,14], bending and fracture [15], and compression pillars [16,17,18,19,20]. Uniaxial compression pillars are among the most commonly used specimen geometries because their stress state is relatively easy to understand compared to indentation, and they are relatively easy to fabricate as compared to tensile, bend, and fracture geometries [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is a significant concern in fundamental science and a wide variety of applications, including geophysical solid deformation [3], machinability [2], and the design of reliable materials [4][5][6]. In particular, deformation localization is widely observed in irradiated materials, where the phenomenon is manifest in the formation of defect-free dislocation channels, which can lead to drastic deterioration of structural materials in nuclear energy [4,[7][8][9]. Extensive experimental and modelling efforts have been carried out to shed light on the mechanisms which lead to irradiation-induced deformation localization [4,[7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…In particular, deformation localization is widely observed in irradiated materials, where the phenomenon is manifest in the formation of defect-free dislocation channels, which can lead to drastic deterioration of structural materials in nuclear energy [4,[7][8][9]. Extensive experimental and modelling efforts have been carried out to shed light on the mechanisms which lead to irradiation-induced deformation localization [4,[7][8][9][10][11][12]. It has been found that during plastic deformation, the movement of dislocations may sweep away, absorb or destroy irradiation-produced defects.…”
mentioning
confidence: 99%